2022
DOI: 10.1007/s11469-022-00825-x
|View full text |Cite
|
Sign up to set email alerts
|

Need Frustration, Gaming Motives, and Internet Gaming Disorder in Mobile Multiplayer Online Battle Arena (MOBA) Games: Through the Lens of Self-Determination Theory

Abstract: Playing mobile MOBA games has become a popular leisure activity among Malaysian youth. However, MOBA games are highly addictive and have negative impacts on adult development. Inadequate local studies investigated the risk factors of excessive MOBA gameplay. The present study examined the (1) predictive role of need frustration on Internet gaming disorder (IGD) and (2) mediating effect of gaming motives. A total of 398 mobile MOBA gamers aged 18 to 29 participated in this cross-sectional online survey study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Frustration is an extra obstacle that may impede the problem-solving capabilities of video game players. Repeatedly failing to complete a level or challenge may result in player frustration and hinder their capacity to employ critical and creative thinking in order to devise solutions (35). Frustration has the potential to impair players' problem-solving capabilities, dull their motivation, cloud their judgment, and impede their ability to surmount obstacles and advance in the game.…”
Section: Challenges To Problem-solving Abilities In Video Game Playersmentioning
confidence: 99%
“…Frustration is an extra obstacle that may impede the problem-solving capabilities of video game players. Repeatedly failing to complete a level or challenge may result in player frustration and hinder their capacity to employ critical and creative thinking in order to devise solutions (35). Frustration has the potential to impair players' problem-solving capabilities, dull their motivation, cloud their judgment, and impede their ability to surmount obstacles and advance in the game.…”
Section: Challenges To Problem-solving Abilities In Video Game Playersmentioning
confidence: 99%
“…This may occur, for example, if one finds little enjoyment in day-to-day activities, struggles athletically or academically, or has few friends or supportive family members. Thwarted needs are a risk factor for PG (Mills & Allen, 2020 ; T’ng et al, 2022 ). In contrast, a person’s ability to meet psychological needs outside of video games, or need satisfaction , protects against PG (Mills & Allen, 2020 ).…”
Section: Basic Psychological Needs and Their Relation To Healthy And ...mentioning
confidence: 99%
“…MOBA games constitute a significant segment of the rapidly expanding and captivating eSports genre, closely intertwined with players’ social experiences ( Wang et al, 2023 ). This connection has led to widespread criticism of the genre, citing perceived adverse effects on players’ physical and psychological well-being, lifestyle, and work-study balance ( T’ng et al, 2023 ). However, recent pro-game research on the genre has challenged these assumptions, highlighting MOBA games for their potential to foster cultural inclusiveness, enhance social connectedness, alleviate stress, boost cognitive skills, and facilitate skill transferability ( Mora-Cantallops and Sicilia, 2018 ; Wang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have identified various factors contributing to gaming addiction ( Nuyens et al, 2016 ; Xia et al, 2019 ; Lieberoth and Fiskaali, 2021 ; Wut et al, 2021 ). MOBA games, such as LoL and Honor of Kings (HOK) in China, in particular, have gained notoriety for their adverse effects on gamers, including user retention problems ( Wang et al, 2023 ) and the promotion of gaming disorder through frustration-induced continuance ( T’ng et al, 2023 ). To address and manage gaming disorder more effectively, researchers have proposed theoretical models based on diverse perspectives and measurement methods.…”
Section: Introductionmentioning
confidence: 99%